Intervención multimedia artística inspirada en la cultura Panzaleo - Paucar Pico, Junior Vicente (2020)
This project addressed the problem of dissemination of the generative project Panzaleo, of the Technical University of Cotopaxi, proposing a multimedia product (videomapping) as a communication tool of the generative project, an audiovisual proposal that is based on the morphological study of the iconographic modules that make up the decoration of the Panzaleo vessels, which represent their relationship with nature, astrology, mythology, worldview and knowledge of compositional forms and structures. By reinterpreting and digitizing the iconography of the vessels, digital animations were carried out in 2D and 3D, to be projected onto a rigid support obtained from the combined selection of two vessels from the Panzaleo project, built of metal and painted white. The development of this intervention seeks to make known the generative project Panzaleo and the visual value of its iconography. The project contains research techniques such as: bibliographic, documentary and field that were executed for the recognition of the place where the projection will take place. In addition, interviews were conducted with experts on topics such as audiovisual production, videomapping applied to cultural themes, and cultures and pre-Columbian including Panzaleo, aimed at determining the viability of the project. The methodology of Robert Gillam was used to determine the form of the support and the methodology of Dario Saeed for the realization of the multimedia product.